2014
DOI: 10.1159/000362242
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Brain-Derived Neurotrophic Factor as a Biomarker of Executive Functioning

Abstract: Background/Aims: Neurotrophins such as brain-derived neurotrophic factor (BDNF) are vital for neuronal survival and adaptive plasticity. With high BDNF gene expression in the prefrontal cortex, BDNF is a potential regulatory factor for building and maintaining cognitive reserves. Recent studies suggest that individual differences in executive functioning, a broad cognitive domain reliant upon frontal lobe structure and function, are governed in part by variance in BDNF polymorphisms. However, as neurogenetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
3
21
1
Order By: Relevance
“…Our results are congruent with previous data reported in both animal and human studies that documented an association between BDNF-related activity and cognitive functioning (Koven and Collins, 2014 ; Robbins and Cools, 2014 ), particularly with data suggesting a specific association with abilities in the executive system domain (Gajewski et al, 2011 ; Alfimova et al, 2012 ; Lu et al, 2012 ; Tükel et al, 2012 ; Koven and Collins, 2014 ). In fact, molecular studies reported that the BDNF gene polymorphism (Val66Met) may affect executive functions in healthy subjects (Alfimova et al, 2012 ) and in patients with psychiatric disturbances (Lu et al, 2012 ; Tükel et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results are congruent with previous data reported in both animal and human studies that documented an association between BDNF-related activity and cognitive functioning (Koven and Collins, 2014 ; Robbins and Cools, 2014 ), particularly with data suggesting a specific association with abilities in the executive system domain (Gajewski et al, 2011 ; Alfimova et al, 2012 ; Lu et al, 2012 ; Tükel et al, 2012 ; Koven and Collins, 2014 ). In fact, molecular studies reported that the BDNF gene polymorphism (Val66Met) may affect executive functions in healthy subjects (Alfimova et al, 2012 ) and in patients with psychiatric disturbances (Lu et al, 2012 ; Tükel et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, molecular studies reported that the BDNF gene polymorphism (Val66Met) may affect executive functions in healthy subjects (Alfimova et al, 2012 ) and in patients with psychiatric disturbances (Lu et al, 2012 ; Tükel et al, 2012 ). Very interestingly, Koven and Collins ( 2014 ), who adopted a design similar to ours, recently documented a significant relationship in healthy subjects between (urinary) BDNF concentration and performance on executive tests. These authors examined a sample of more than 50 healthy young subjects who were administered a neuropsychological test battery investigating different subcomponents of the executive system.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations